Types of serve stance and height of players. A study of the best servers in history - Vila Pascual, J. (Coaching and Sport Science Review, 2023)
One of the most important performance indicators in tennis is the serve. While recognising the great relevance of this stroke, the objectives of this study were to investigate: the effect of the height of the players on the serve, the two types of stances in the serve (feet up and feet back) and, finally, to study if there was a relationship between the height of the players and the use of these stances in the serve. All this, on a sample of the 50 best servers by effectiveness in the history of the ATP. The results obtained highlighted the great importance of the height of the tennis player in the service. In addition, 72% of these best servers used the feet up stance, which implies greater advantages of this stance over the feet back stance. Finally, it was observed that the taller the players were, the more they used the feet up stance. On the other hand, the shorter the height of the players, the more frequently they used the foot back stance. Based on these results, it could help coaches to recommend one stance or the other, depending on the height and style of play of the players.